Design and Development of an X4-ROV - Zainah, Md. Zain; Maziyah, Mat Noh; Khairul Ashraff, Ab Rahim; Nurfadzillah, Harun (2016)

(untitled)
Remotely operated vehicle (ROV) is an unmanned underwater vehicle (UUV) used for conducting underwater task to replace a human diver in the risky job. X4-ROV is a micro observation class ROV to be used mainly for visual observation of underwater structure or environment by utilizing a high definition web camera. The designed vehicle structure was aims towards portability and maneuverability in attitude motions of roll, pitch, and yaw, and the translational motion forward/reverse/lateral. This work explains the use and modification of an open-source platform (OpenROV) into X4-ROV system